The Role of Nurses in Managing Self-Care for Diabetes Mellitus Patients in Surgical Medical Services: A Literature Review - Tommy Pangandaheng (Health & Medical Sciences, 2026)
This study aims to explore the role of nurses in managing self-care among patients with diabetes mellitus in medical-surgical services through a comprehensive literature review. Using a qualitative descriptive design, the research employed a library-based approach that analyzed 22 peer-reviewed articles published between 2019 and 2025. Data were collected through systematic literature tracing, document analysis, and thematic synthesis to identify recurring patterns in nursing interventions related to diabetes self-care management. The analysis revealed five dominant thematic areas: (1) diabetes self-management education (DSME), (2) psychosocial and spiritual support, (3) wound and foot care management, (4) family involvement in self-care, and (5) integration of health information technology. The findings demonstrate that nurses play a central role as educators, motivators, and care coordinators in improving patient self-efficacy, treatment adherence, and glycemic control. Moreover, the integration of family support and digital health interventions enhances continuity of care and patient empowerment. These results reinforce the relevance of Orem’s Self-Care Deficit Nursing Theory and Bandura’s Self-Efficacy Theory in nursing practice while providing evidence for the holistic and transformative contributions of nurses in chronic disease management. The study concludes that advancing interprofessional collaboration, digital health integration, and culturally sensitive approaches are essential to optimizing diabetes self-care outcomes and enhancing nursing professionalism.